2005
DOI: 10.1227/01.neu.0000163603.70972.ab
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Resection of Intrinsic Insular Tumors

Abstract: This report, with an accompanying videotape, details the authors' technique for performing radical resections of tumors intrinsic to the insular lobe. The resection technique takes advantage of the fact that many intrinsic insular tumors grow within the confines of the insula, usually without violating pial borders or invading the medial structures. The method described is based on an anatomic dissection of the insula that uses the internal boundaries of the region, particularly the peri-insular sulci, as guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
70
0
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 8 publications
3
70
0
9
Order By: Relevance
“…12,17,22,35,38,39,44 In our series, no ischemic lesion was attributed to an LLA interruption. The ischemic lesions typically encountered after insular corticectomies were linked to injuries of long perforating branches of the M 2 segments of the MCA.…”
Section: Discussionmentioning
confidence: 45%
“…12,17,22,35,38,39,44 In our series, no ischemic lesion was attributed to an LLA interruption. The ischemic lesions typically encountered after insular corticectomies were linked to injuries of long perforating branches of the M 2 segments of the MCA.…”
Section: Discussionmentioning
confidence: 45%
“…Nonetheless, several reports in the past decade have demonstrated that it was possible to perform insular glioma resection with substantial but acceptable complication rates. 12,17,23,25,29,33,38,39,47,50,53,54 Surprisingly, most of these studies were mainly focused on motor function, in particular with the use of intraoperative motor tract monitoring, 40 while possible language disturbances have not been accurately assessed using an extensive and longitudinal examination by a speech therapist. In this paper, we report for the first time the results of an objective language examination performed by a speech therapist before, during, immediately after, and 3 months after an awake surgery for a Grade II glioma involving the dominant insula in a homogeneous series of 24 patients.…”
Section: Sulamentioning
confidence: 99%
“…12,17,23,25,29,33,38,39,47,50,53,54 However, these patient series were essentially focused on motor function, in particular with the use of intraoperative motor tract monitoring, 39 whereas possible language disorders have received less attention. No previous studies have accurately assessed language disturbances using objective and longitudinal examination by a specialist before, during, and after surgery (immediately and at 3 months) within the dominant insula.…”
mentioning
confidence: 99%
“…Functional guidance using a bipolar subcortical stimulation has been employed by several groups. 5,15,17,23,32 It has been described as a useful mapping tool for identifying the deep motor tracts at the medial and dorsal part of insular gliomas but it does not allow monitoring of the function.The purpose of this study was to establish a protocol in which we could use both modalities, TCES for monitoring and subcortical stimulation for mapping. For this purpose, we modified the monopolar stimulation technique for subcortical stimulation.…”
mentioning
confidence: 99%
“…Functional guidance using a bipolar subcortical stimulation has been employed by several groups. 5,15,17,23,32 It has been described as a useful mapping tool for identifying the deep motor tracts at the medial and dorsal part of insular gliomas but it does not allow monitoring of the function.…”
mentioning
confidence: 99%